The Persuasive Appeal of Provider-Patient Interaction in the Acceptance of COVID-19 Vaccine at a Health Service Unit in Isabela - Suayan, Maria Angelyne (Journal of Interdisciplinary Perspectives, 2024)
The study examined the persuasive appeal of provider-patient interactions in a health service unit in Isabela, focusing on vaccine acceptance. Using the Aristotle Rhetoric triangle framework, it analyzed the effectiveness of Logos, Pathos, and Ethos in influencing vaccine acceptance across different demographic groups. A mixed-methods descriptive design was employed, with quantitative data collected through surveys and qualitative data through focus interviews. The findings indicate that vaccine acceptance and hesitancy are complex and influenced by various factors including age and education. While healthcare providers effectively employ persuasive appeals, they may not significantly influence vaccine acceptance across different groups. Post-rollout opinions on the vaccine correlate with pre-rollout health beliefs, highlighting the importance of ongoing outreach and education efforts. Tailored communication strategies are crucial, addressing concerns among younger age groups and ensuring continuous training for healthcare providers. Additionally, factors beyond provider-patient interaction should be considered, including community engagement programs and long-term follow-up studies. Implementing these recommendations can effectively address vaccine hesitancy and promote widespread acceptance of the COVID-19 vaccine.